CRISPR/Cas9 mediated gene editing in non-model nematode Panagrolaimus sp. PS1159 - Hellekes, Viktoria; Claus, Denise; Seiler, Johanna; Illner, Felix; Schiffer, Philipp H.; Kroiher, Michael (Frontiers in Genome Editing, 2023)
The phylum Nematoda consists of a huge diversity of species in a broad range of ecosystems and habitats. Nematodes share a largely conserved Bauplan but major differences have been found in early developmental processes. The development of the nematode model organism Caenorhabditis elegans has been studied in great detail for decades. These efforts have provided the community with a large number of protocols and methods. Unfortunately, many of these tools are not easily applicable in non-Caenorhabditis nematodes. In recent years it has become clear that many crucial genes in the C. elegans developmental toolkit are absent in other nematode species. It is thus necessary to study the developmental program of other nematode species in detail to understand evolutionary conservation and novelty in the phylum. Panagrolaimus sp. PS1159 is a non-parasitic nematode exhibiting parthenogenetic reproduction and we are establishing the species to comparatively study evolution, biodiversity and alternative reproduction and survival strategies. Here, we demonstrate the first successful application of the CRISPR/Cas9 system for genome editing in Panagrolaimus sp. PS1159 and its closely related hermaphroditic species Propanagrolaimus sp. JU765 with both the non-homologous end joining and the homology-directed repair mechanism. Using microinjections and modifying published protocols from C. elegans and P. pacificus we induced mutations in the orthologue of unc-22, which resulted in a visible uncoordinated twitching phenotype. We also compared the HDR efficiency following the delivery of different repair templates. This work will expand the applicability for a wide range of non-model nematodes from across the tree and facilitate functional analysis into the evolution of parthenogenesis, changes in the developmental program of Nematoda, and cryptobiosis.